A nickel/organoboron catalyzed metallaphotoredox platform for C(sp2)–P and C(sp2)–S bond construction. Issue 4 (18th January 2022) - Zhu, Yuan; Zu, Weisai; Tian, Qing; Cao, Zifeng; Wei, Yu; Xu, Liang
Abstract : A boron-based organic photocatalyst has been applied in metallaphotoredox catalyzed C–P and C–S bond construction reactions. Abstract : Herein, an organoboron photocatalyst, aminoquinolate diarylboron (AQDAB), is utilized collaboratively with a nickel catalyst in metallaphotoredox catalyzed C(sp 2 )–P and C(sp 2 )–S cross-coupling reactions. This strategy effectively couples aryl halides with diarylphosphine oxides and thiols at room temperature under an air atmosphere, affording the corresponding triarylphosphine oxides and thioethers in generally moderate to good yields.